Assessment of Oocyte Retrieval and its Quality from the Abattoir Ovaries of Jaffarabadi Buffaloes by Aspiration and Slicing Methods - Parmar, Kiran H.; Raval, Rupesh J.; Vala, Karshan B.; Patbandha, Tapas (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Present study was carried out to assess the efficacy of aspiration and slicing methods of oocytes retrieval, retrieval rate and grades of oocytes recovered from the abattoir ovaries of culled Jaffarabadi buffaloes. The ovaries were procured from local abattoir (n=100), and the oocytes from 50 ovaries each were retrieved by slicing and aspiration method, which yielded 205 and 148 oocytes of different grades, respectively. Among the two methods of oocytes retrieval, the slicing method yielded significantly (P
Keywords: Aspiration; Buffaloes; Oocytes grades; Ovary; Retrieval rate; Slicing